Age-related increase of mitochondrial content in human memory CD4+ T cells contributes to ROS-mediated increased expression of proinflammatory cytokines - Chen, Yuling; Ye, Yuanchun; Krauß, Pierre-Louis; Löwe, Pelle; Pfeiffenberger, Moritz; Damerau, Alexandra; Ehlers, Lisa; Buttgereit, Thomas; Hoff, Paula; Buttgereit, Frank; Gaber, Timo (Frontiers in Immunology, 2022)
Cellular metabolism modulates effector functions in human CD4+ T (Th) cells by providing energy and building blocks. Conversely, cellular metabolic responses are themselves modulated by various influences, e.g., age. Thus, we hypothesized that metabolic reprogramming in human Th cells during aging modulates effector functions and contributes to “inflammaging”, an aging-related, chronic, sterile, low-grade inflammatory state characterized by certain levels of proinflammatory cytokines. Analyzing the metabolic response of human naive and memory Th cells from young and aged individuals, we observed that memory Th cells exhibit higher glycolytic and mitochondrial fluxes than naive Th cells. In contrast, the metabolism of the latter was not affected by donor age. Memory Th cells from aged donors showed a higher respiratory capacity, mitochondrial content, and intracellular ROS production than those from young donors without altering glucose uptake and cellular ATP levels, which finally resulted in higher secreted amounts of proinflammatory cytokines, e.g., IFN-γ, IP-10 from memory Th cells taken from aged donors after TCR-stimulation which were sensitive to ROS inhibition. These findings suggest that metabolic reprogramming in human memory Th cells during aging results in an increased expression of proinflammatory cytokines through enhanced ROS production, which may contribute to the pathogenesis of inflammaging.